Hematopoietic activity of rat bone marrow at the influence of salt extract of Hirudo verbana Carena, 1820 - Aminov, R. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2018)
The mitotic activity of the bone marrow of non-linear female rats after feeding their offspring was studied and this index was estimated in their offspring in the early stages of postembryonic development – on the 1, 15, 30, 45, 60th day. Females two weeks prior to mating with males and two weeks after were intraperitoneally injected with Hirudo verbana saline extract (5 mg/kg of the weight of an animal), once, every week. In the experimental group of females, the mitotic index significantly increased (by 33.61%); in their offspring, the maximum increase in the mitotic index was observed on the first day (by 50.88%); the increase in the proliferative activity of bone marrow cells was observed at other observation times: on the 30th day (by 25.67%) and on the 60th day (by 18.35%). In the experimental group of animals, all hematopoietic parameters of peripheral blood (the number of leukocytes, erythrocytes, hemoglobin) also increased. An increase in the number of leukocytes in the experimental group of females occurred without significant changes in their relative population ratios in the leukocyte blood formula. In the experimental group of the offspring, the effect of the leech extract on the changes in the differentiation of leukocyte populations was revealed. Thus, in the offspring for the first day the shift of the leukocyte blood formula to the left decreased due to the decrease in cells of innate immunity (granulocytes and monocytes) and increase in adaptive immunity cells (lymphocytes), which indicates an accelerated differentiation of the lymphoid system towards adult animals. Some differences in the differentiation of leukocytes were noted at the onset of sexual maturation (on the 30th day) and at its end (on the 60th day). At these times, a neutrophilic shift occurred to the left, as a consequence of the intension of the congenital link of immunity in the presence of an adequate number of cells of adaptive immunity. Thus, as a result of the study, the stimulating effect of the extract of the medical leech on the mitotic activity of the bone marrow was revealed, both in mature females and in their offspring, which resulted in an increase in the number of leukocytes, erythrocytes, hemoglobin, and color index. In the offspring, during the period of increased stress of morphogenesis, there is an activation of both the congenital and adaptive links of immunity in the experimental group of animals.